Optimal Scheduling of Solar-Wind-Thermal Integrated System Using α-Constrained Simplex Method - Sunimerjit Kaur; Yadwinder Singh Brar; Jaspreet Singh Dhillon (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
In this paper, multi-objective economic-environmental solar-wind-thermal power scheduling model was developed and it was optimized for five test systems. First test system was based upon a purely thermal power generating system and its problem was formulated to satisfy three conflicting objectives: (i) fuel cost, (ii) emission, and (iii) emission. The second, third and fourth test systems were comprised of optimal scheduling of integrated solar-thermal, wind-thermal and solar-wind-thermal power systems, respectively. Uncertainty costs were also considered in the renewable power based systems. These four test systems were examined for five power demands i.e. 200 MW, 225 MW, 250 MW, 275 MW, & 300 MW. Fifth test system was also deployed upon a renewable-thermal power scheduling. The effects of variation in number of thermal generators on fuel cost and emission were perceived, for a power demand of 400 MW. The values of fuel cost (4067.98 Rs/h) and emission (2,441.05 kg/h) reduced to 3,232.94 Rs/h and 1,939.30 kg/h, respectively, when number of thermal generators were reduced from four to two. The -constrained simplex method (ACSM) was used for simulation and the results were compared with simplex method (SM). The results clearly depict the dominance of ACSM over SM in almost all the fields.